Academic fraud investigation using fraud diamond: Evidence from accounting students - Moh. Riskiyadi (Institute of Accounting Research and Novation (IARN), 2025)
This study aims to investigate academic fraud committed by students using the fraud diamond. The elements of the fraud diamond, comprising pressure, opportunity, rationalization, and capability, are utilized to examine academic fraud perpetrated by accounting students. This study employed a quantitative method with a purposive sampling technique of 200 accounting students attending universities in Madura. The results show that each element of the fraud diamond — namely, pressure, opportunity, rationalization, and capability — has a significant positive influence on academic fraud. Simultaneously, all aspects of the fraud diamond have a significant positive influence on academic fraud. This study is expected to provide references for further research and suggestions for university academics, aiming to mitigate academic fraud.